Independent living in adults with autism spectrum disorder: Stakeholders' perspectives and experiences. (December 2021) - Ghanouni, Parisa; Quirke, Stephanie; Blok, Jennifer; Casey, Amanda
Highlights: This study involved relevant stakeholders, including adults on the spectrum, to explore barriers to independent living. Psychophysical factors, financial constraints, and community integration can serve as significant challenges. There is a need to implement programs and services aimed at facilitating the independent living for adults with ASD. Abstract: Independent living is a basic human right that enables individuals with disabilities to determine where they live, who they live with and what kind of support that they receive. Limited research exists regarding the challenges that adults with autism spectrum disorder (ASD) may face when attempting to live independently. Given the importance of independent living for adults with ASD, this study aimed to examine the perspectives of stakeholders about independent living among adults with ASD. Methods: We recruited a total of 19 stakeholders including adults with ASD and parents of adults with ASD from Canadian provinces. In-depth, semi-structured interviews were conducted to identify factors affecting independent living among adults with ASD. Interviews were transcribed and analyzed using thematic analysis to identify overarching themes. Results: Three themes emerged in our findings, including: a) Psychophysical stability and daily living; b) Financial management and planning; and c) Integrated community living and independence. Conclusion: The findings from this study suggest that adults with ASD face several challenges related to independent living. Factors related to psychophysical stability and daily living, financial management, and integrated community living and housing were all found to influence the ability of adults with ASD to live independently. By exploring stakeholders' perspectives of independent living for adults with ASD, this study provides some insight that can help inform the development of programs and services to facilitate independent living for adults with ASD.